Continuous Threat of Growing Antimicrobial Resistance Among Salmonella Typhi Isolates: A Multicenter Study from Pakistan - Hussain, Ashfaq; Farooq, Muhammad; Satti, Muhammad Luqman; Hanif, Faisal; Sarwar, Saba; Sana, Fatima (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine current susceptibility patterns of Salmonella enterica serovar Typhi (S. Typhi) in four cities of Pakistan and to deduce the frequency of multidrug resistant, extensively drug-resistant S. Typhi. Study Design: Cross-sectional study. Place and Duration of Study: Departments of Microbiology, Pakistan Navy Ship Shifa Hospital, Karachi, Pak Emirates Military Hospital, Rawalpindi, Combined Military Hospital, Sialkot, Combined Military Hospital, Abbottabad, Pakistan, from Apr 2019 to Sep 2020. Methodology: Blood culture specimens of patients with suspected Enteric fever from four different institutes were received in respective laboratories. Culture and identification of isolates were done and specimens yielding growth of S. Typhi, were included in the study. Antibiotic susceptibility was tested according to Clinical and Laboratory Standards Institute guidelines 2019 and 2020. Results: A total of 970 blood culture specimens yielded growth of S. Typhi. Maximum isolates were found from Pak Emirates Military Hospital, Rawalpindi, 395(40.7%) followed by Pakistan Navy Ship Shifa, Karachi 366(37.7%). The total number of multidrug resistant isolates were 679 (70%) and extensively drug resistant isolates were 457(47.1%) with maximum number of multidrug resistant and extensively drug resistant S. Typhi from Pakistan Navy Ship Shifa. Ciprofloxacin susceptible isolates were 50(5.2%) and maximum sensitive isolates were from Combined Military Hospital, Abbottabad. Resistance to azithromycin was found in four isolates (0.4%). There were no isolates resistant to meropenem. Conclusion: Emergence of antibiotic resistance among S. Typhi strains is a threat which emphasizes the importance of surveillance of antimicrobial susceptibility patterns and amendment of current antibiotic prescribing practices.